The microenvironment in chronic pancreatitis and pancreatic cancer induces neuronal plasticity - Demir, Ihsan Ekin; Ceyhan, Güralp Onur; Rauch, Ulrich; Altintas, Burak; Klotz, M.; Müller, Michael W.; Büchler, Markus W.; Friess, Helmut; Schäfer, Karl Herbert (Neurogastroenterology and motility, 2010)
BACKGROUND: Pancreatic neuropathy in chronic pancreatitis (CP) and pancreatic cancer (PCa) is characterized by pancreatic neuropathy, i.e. increased neural density and hypertrophy, which are associated with neuropathic pain. To better understand the mechanism of these neuropathic alterations, we aimed at achieving an in-vitro simulation of the intrapancreatic neuroplasticity. - METHODS: Dissociated myenteric plexus (MP) and dorsal root ganglia (DRG) neurons of newborn rats were treated with normal human pancreas (NP), CP or PCa tissue extracts. Furthermore, MP and DRG neurons were cultured in supernatants from different pancreatic cancer cell lines (PCC) and human pancreatic stellate cells (hPSC) obtained from either CP or PCa tissues. For analysis, the neurite density, outgrowth, neuronal branching capacity and perikaryonal size were quantified. - KEY RESULTS: Myenteric plexus and DRG neurons grown in CP and PCa tissue extracts built denser networks than in NP extracts. Both neuronal types showed a strong neurite outgrowth, more complex branching pattern and a somatic hypertrophy in CP and PCa extracts. Pancreatic cancer cell supernatants induced a prominent neurite outgrowth, increased neurite density and perikaryonal hypertrophy in MP and DRG neurons. Supernatants of CP-derived hPSC strongly stimulated neurite outgrowth. Glial density in MP cultures was strikingly increased by PCa tissue extracts. - CONCLUSIONS & INFERENCES: Intrapancreatic microenvironment in CP and PCa induces neuroplastic alterations under in-vitro conditions, leading to increased neural density and hypertrophy. Thus, due to its neurotrophic attributes, the intrapancreatic microenviroment in CP and PCa seems to be a key player in the generation of pancreatic neuropathy and neuroplasticity.
Gesehen am 05.01.2024